Reshaping universities for survival in the 21st century : new paradigms and opportunities - Chow, Christina; Leung, Clement (Bentham Science Publishers, 2016)
Universities are facing unprecedented challenges in the 21st century. The international landscape of higher education is undergoing profound changes. These ancient institutions which represent the ultimate manifestation of human civilization are now confronted with dramatic changes as a result of globalisation, the knowledge economy and rapid technological advances. The traditional role of the university is forced to transform to meet these new expectations and challenges. This book provides an impartial insight into the challenges faced by higher education in the 21st century. It also suggests possible paths which universities might take to survive.